Unveiling the Link between Customer Experience and Customer Loyalty on Blibli: The Mediating Role of Trust - Yusiana, Rennyta; Hurriyati, Ratih; Dirgantari, Puspo Dewi (PT. Riset Press International, 2024)
The rapid growth of digital technology and the Internet has opened new avenues for business, particularly in the field of e-commerce. Online shopping has become the prevailing trend for purchasing goods and services, reshaping market dynamics. Blibli.com is a subsidiary of Djarum in the digital sector established in 2010 and is the original Indonesian e-commerce company that focuses on building the shopping ecosystem of choice for consumers and institutions through a secure omnichannel commerce platform. However, in a highly competitive environment, maintaining and increasing customer loyalty is a challenge. This study aims to explore the effect of customer experience on Blibli customer loyalty in Indonesia, with customer trust as an intermediary variable. This research uses a quantitative descriptive approach and path analysis, with a sample of 200 respondents who are Blibli application users. The results showed that customer experience and trust have a significant influence on customer loyalty. Data analysis shows that Blibli's app design, appearance, navigation, and payment process is highly rated by customers. Customers also had a positive emotional experience and high trust in Blibli's customer service and social media presence. This study also found that customer trust plays a role as a mediator in the relationship between customer experience and customer loyalty. Based on these findings, this study suggests Blibli to focus on increasing customer trust through improving customer experience to drive customer loyalty.